Diagnostika a lécba BCR/ABL-negativních myeloproliferativních onemocnení--principy a výchdiska doporuceni CZEMP - Schwarz, J; Penka, M; Campr, V; Pospísilová, D; Kren, L; Nováková, L; Bodzásová, C; Brychtová, Y; Cerná, O; Dulícek, P; Joniásová, A; Kissová, J; et al. (Vnitrni lekarstvi, 2011)
In 2009, the recommendations of the Czech Collaborative Group for Ph- Myeloproliferative Diseases (CZEMP) for diagnosis and treatment of BCR/ABL-negative myeloproliferative diseases (MPD), i.e., essential thrombocythemia (ET), polycythaemia vera (PV) and primary myelofibrosis (PMF) were updated and extended. The present article gives the rationale of the recommendations in full detail. The CZEMP diagnostic criteria for ET and PMF are based on histopathological (HP) findings, which must unconditionally be in line with the given clinical and laboratory characteristics of ET or of a certain stage of PMF, respectively. The platelet count is not decisive for diagnosis. In cases lacking an adequately taken and read HP finding, the Polycythemia Vera Study Group (PVSG) criteria are recommended. The diagnosis of typical PV is based on demonstration of the V617F mutation of the JAK2 gene along with a significant increase of red cell parameters. If these are close to borderline, the demonstration of increased total red cell mass (RCM) is required. In atypical cases lacking polyglobulia or elevated RCM, the HP picture of PV (in accordance with WHO description) plus JAK2 V617F mutation is satisfactory for diagnosis, or, in cases lacking JAK2 V617F mutation, the HP picture of PV along with polyglobulia (or increased RCM) is sufficient. The treatment principles of ET and other MPDs with thrombocythemia (MPD-T; i.e., the early stages of PMF and PV) are identical. The patients are stratified by their thrombotic risk (preceding thrombosis, another thrombophilic state, jAK2 mutation), presence of disease symptoms (mainly microcirculatory), platelet count and age. Only patients up to 65 years lacking the above mentioned risks with a platelet count < 1000 x 10(9)/l are considered as low-risk and do not demand cytoreducing therapy. The others are high-risk ones and have an indication for thromboreduction. In patients older than 65 years, the potentially leukemogenic drug hydroxyurea (HU) may be used. In the younger ones, the choice is between anagrelide (ANG) or interferon-alpha (IFN). In high-risk patients, the treatment goal is to maintain platelet counts below 400, and in low-risk ones, below 600 x 10(9)/l. In PV, polycythemia itself is another thrombotic risk factor. The condition is treated by bloodletting or erythrocytaphereses. If hematocrit levels < or =45 are not achieved, cytoreductive therapy using HU in patients over 65 years, or IFN in younger individuals is required. All patients with thrombocythemia in PV are high-risk and have an indication for cytoreduction. Acetylsalicylic acid is given to all patients with MPD-T with platelets < 1000 x 10(9)/l (at higher counts, hemorrhage is imminent), and to all individuals with PV, unless contraindication is present. In case of platelet count normalization, it may be withdrawn in cases of low-risk ET or PMF, not in JAK2+ PV. The treatment of advanced stages of PMF is symptomatic, with substitution of blood derivatives being the basis. The only curative treatment is allogeneic stem cell transplantation, which should not be indicated too early seeing to its risks, but also not too late--we must not allow transition into acute leukemia, which is heralded by blasts in the blood picture. The indication is the presence of any of the following criteria: values of hemoglobin < 10 g/dl, WBC < 4 x 10(9)/l and platelets < 100 x 10(9)/l, any percentage of blasts or > or = 10% immature granulocytes in the differential picture, >1 erythroblast per 100 cells--all at repeated examinations within at least a 2-month interval, and in addition, rapid progression of hepato-/splenomegaly, presence of general symptoms of the disease, portal hypertension and extensive swellings.
Keywords: polycythaemia vera; směrnice pro lékařskou praxi jako téma; bcr-abl fúzní proteiny; Thrombocythemia, Essential; lidé; Practice Guidelines as Topic; myeloproliferativní poruchy; Polycythemia Vera; primární myelofibróza; Humans; Myeloproliferative Disorders; esenciální trombocytemie; Fusion Proteins, bcr-abl; Primary Myelofibrosis